2014
DOI: 10.1002/asia.201402102
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Crystal Packing, and Ambipolar Carrier Transport Property of Twisted Dibenzo[g,p]chrysenes

Abstract: A versatile method for the synthesis of dibenzo[g,p]chrysene (DBC) derivatives based on regio- and stereoselective stannyllithiation to diarylacetylenes is described. This method affords a variety of DBCs possessing both electron-donating and electron-withdrawing functional groups. These twisted molecules take brickwork packing structures in single crystals. Thus, ambipolar carrier transport properties with mobility values of up to 10(-3)  cm(2)  V(-1)  s(-1) in the amorphous state were achieved. Functional gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…The successful preparation of single crystals of 9 , 12 and 14 allowed the determination of their molecular structures by X-ray diffraction analysis ( Supplementary Figs 5–7 ). Compounds 9 and 12 , containing multiple dibenzo[ g , p ]chrysene 28 moieties, adopt a highly twisted structure and feature a curved π -conjugated skeleton ( Supplementary Figs 5 and 6 ). Using a procedure similar to that for bifunctional acetylenes, 1,4-diphenylbuta-1,3-diyne ( 1 7) could be benzannulated with 1 to afford 10,10′-diphenyl-9,9′-biphenanthrene ( 18 ) 29 in 80% isolated yield ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The successful preparation of single crystals of 9 , 12 and 14 allowed the determination of their molecular structures by X-ray diffraction analysis ( Supplementary Figs 5–7 ). Compounds 9 and 12 , containing multiple dibenzo[ g , p ]chrysene 28 moieties, adopt a highly twisted structure and feature a curved π -conjugated skeleton ( Supplementary Figs 5 and 6 ). Using a procedure similar to that for bifunctional acetylenes, 1,4-diphenylbuta-1,3-diyne ( 1 7) could be benzannulated with 1 to afford 10,10′-diphenyl-9,9′-biphenanthrene ( 18 ) 29 in 80% isolated yield ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…We have demonstrated an unprecedented reaction of organoboron compounds, which allows the facile transformation of acetylenes into non-planar, curved three-dimensional π -conjugated molecules. Such curved and/or twisted π -conjugated systems have recently received considerable attention, as they can exhibit dynamic structural changes 30 31 32 , chiroptical properties 33 34 35 and characteristic assembling behaviour, which may be beneficial for applications in organic electronics 28 36 . Besides the synthetic utility, the sequential nature of this protocol, featuring the insertion of an alkyne (1,2-carboboration) into a B–C bond, followed by an oxidative deborylation/C–C coupling reaction, sets it substantially apart from hitherto known reactions mediated by main group elements.…”
Section: Discussionmentioning
confidence: 99%
“…Inspired by this observation, we anticipated that if a radical cation forms selectively at the alkene moiety of BPMF by employing appropriate single-electron oxidation systems, the subsequent spirocyclization and 1,2-aryl migration tandem process may take place to give the desired twisted molecule dibenzo[ g , p ]chrysene (DBC), which is an intriguing holding block of discotic molecules, fluorescent and charge carrier-transporting materials. Diverse synthetic methods of the DBC derivatives have been reported, such as oxidation of electron-rich bis(biaryl)acetylenes, oxidation of electron-rich tetraarylethylenes, intramolecular aromatic C–H/C–Br coupling, double Suzuki-Miyaura coupling, and Pd-catalysed coupling of C–H bonds of small PAHs with dimethyldibenzosilole13141519202122232425262728. On the basis of our reaction design, we herein describe a novel dehydrogenative PAH synthetic methodology based on the oxidative spirocyclization and 1,2-aryl migration tandem process.…”
mentioning
confidence: 99%
“…() For example, Winzenberg et al reported the synthesis of dibenzo[ b , def ] chrysene (DBC) as a new class of stable organic semiconductor to be used as high‐efficient solution‐processed photovoltaic cells. () Similarly, field‐effect characteristics of the OFETs based on a series of chrysene derivatives were studied by Kunugi et al() Ambipolar charge transport in twisted dibenzo chrysene was experimentally investigated by Ueda et al() Stevens et al studied the temperature‐mediated polymorphism in 7,14‐bis((trimethylsilyl)ethynyl)dibenzo[ b , def ]‐chrysene (TMS‐DBC) and found that the 2‐dimensional brickwork crystal packing motif exhibited higher mobility (2.1 cm 2 V −1 s −1 ) than that of low‐temperature polymorph with 1‐dimensional slipped stacking packing. () Yu et al designed and synthesized a new series of conjugated polymers containing dibenzo[ def , mno ] chrysene units and found that poly(4,10‐bithiophene‐6,12‐bis(2−decyltetradecyloxy)‐dibezo[ def , mno ] chrysene) with 2 thiophene groups had better charge transport behavior than poly(2,2 ′ −thiophenevinylenthiophene−4,10−[6,12−bis(2−decyltetra−decyloxy)−dibenzo[ def , mno ]chrysene]).…”
Section: Introductionmentioning
confidence: 99%